Synthesis of Fe3O4/ZnO nanoparticles and their application for the photodegradation of anionic and cationic dyes - Długosz, O.; Szostak, K.; Krupiński, M.; Banach, M. (International journal of environmental science and technology (Tehran), 2021)
Multifunctional materials have become an important research subject in recent years. Zinc oxide nanoparticles (ZnO NP) deposited on iron oxide (Fe 3 O 4 ) allow to obtain material with photocatalytic and magnetic properties. The mass share of Fe 3 O 4 in the composite was 30%. Saturation magnetization for this sample was about 9.5 emu/g. The use of magnetic material allows to recover the photocatalyst after the photodegradation process and reuse it. The possibility of recovery of Fe 3 O 4 nanoparticles with a magnet was estimated at 94.80%, while the recovery of Fe 3 O 4 /ZnO achieved 83.91%. The effects of the type of dyes (Methylene Blue, Methyl Orange, Quinoline Yellow, Eriochromic Black T and Trypanic Blue) on their photodegradation efficiency in terms of molar mass of the dye, the solvent in which the processes were carried out and the type of dye charge were investigated. The photocatalytic material showed higher photodegradation activity of dyes while increasing their molar mass. ZnO NPs deposited on Fe 3 O 4 presented 95.61% photocatalytic efficiency against Trypan Blue and 63.02% against Methylene Blue. Increasing the surface area of the catalyst to 39 m 2 /g and the presence of micro-, meso- and macropores had a positive effect on the sorption process of dyes, especially those of larger sizes, allowing their degradation in the photodegradation process.